A COMPARATIVE STUDY OF CONVENTIONAL PID AND FUZZY-PID FOR DC MOTOR SPEED CONTROL - Buswig, Yonis. M. Yonis (Journal of Fundamental and Applied Sciences, 2018)
The development of a Self Tuning Fuzzy proportional done to be compared with the conventional controller that (DC) motor. A simulation study is used to overcome the appearance of nonlinearities and uncertainties in the system with the proposed controller for the armature voltage controlled DC motors. Each parameter of the Fuzzy the fuzzy logic controller. The proportional, integral and derivative (KP,KI,KD) PID controller is being tuned by the controller. Different types of membership functions are evaluated in the fuzzy control and the best performance will be used in Fuzzy comparative analysis with the conventional PID. The FIS editor from MATLAB defines the membership function and the rules. Load disturbances from a variety of speed response and the step response are simulated from different scenarios.